Eufemisme Bahasa Indonesia di Kalangan Remaja di Desa Pentadio Timur Kecamatan Telaga Biru - Hapsa M. Latif; Dakia N. Djou; Salam Salam (Ideas Publishing, 2023)
This research was motivated by a title about the use of subtle language or choosing the right words when interacting. A person can be said to be ethical if he pays attention to polite and courteous language in his speech. The aim of this research is to describe or explain the form and function of Indonesian euphemisms among teenagers in East Pentadio village. The method used is a descriptive method with a qualitative research type. Based on the research results, it was found that the forms of euphemistic expressions used by young people in East Pentadio include abbreviations, foreign terms, metaphors and periphrases. Meanwhile, refined language functions to create a polite and comfortable atmosphere, disguise meaning, and reduce embarrassment. The habit of softening words has become part of society's culture. For this reason, as a cultured society, we are expected to be able to recognize the use of euphemisms. This serves to maintain mutual feelings and comfort in communicating with fellow speakers.